An alternative strategy to prevent hypocalcemia by adding Zeolite A to the prepartum diet of dairy cows - Souza Saraiva de Oliveira, Raphael (Kansas State University, 2021)
Late gestation cows face several challenges related to nutritional needs and physiological and metabolic changes. Colostrogenesis in the last weeks before calving and subsequent milk production in early lactation increase calcium (Ca) requirements. Disruption of Ca homeostasis in the periparturient period leads to hypocalcemia. Although incidence of clinical hypocalcemia can be insignificant compared with other postpartum diseases, half of multiparous cows are affected by subclinical hypocalcemia (SCH). Calcium deficiency alters function of smooth muscle cells and immune response and interferes with several important physiological processes. Cows that experience hypocalcemia are predisposed to postpartum disorders, poor reproductive efficiency, decreased milk production, and increased risk of early culling. A balanced diet before calving can prevent hypocalcemia and improve Ca availability during the periparturient period, maintaining Ca homeostasis. Prevention of hypocalcemia is the most practical and economical approach to minimize its effects. Two strategies demonstrated to increase concentration of Ca after calving are to create a negative dietary cation-anion difference (DCAD) or include synthetic zeolite A to prepartum diets. A study was conducted to compare blood mineral concentrations after parturition, postpartum health, reproductive efficiency, and milk production of cows supplemented with either anionic salts (AS) or synthetic zeolite A (SZA) in the prepartum period. Primiparous (AS = 232, SZA = 223) and multiparous (AS = 325, SZA = 322) dry cows were randomly assigned at enrollment to be supplemented with AS or SZA and were evaluated daily for health disorders and health treatments during the first 60 days in milk (DIM). Cows were monitored until 150 DIM to determine reproductive outcomes and removal from the herd. Blood samples were collected at 0, 48, and 72 h after calving to determine concentrations of Ca, magnesium (Mg), and phosphorus (P) from a subgroup of cows. Four milk tests were conducted during the study and milk production traits were evaluated. Prepartum supplementation with SZA resulted in greater Ca concentrations at parturition and 48 h after parturition compared with supplementation with AS. Phosphorus and Mg concentrations were less at parturition for SZA compared with AS cows at parturition. At 72 h after parturition, no treatment differences were detected for Mg, but P concentration was greater for SZA than AS cows. Multiparous AS cows were more likely to be treated for clinical hypocalcemia (recumbency) than multiparous SZA cows. Multiparous AS cows had greater morbidity of health disorders than primiparous AS cows, but no parity differences were detected in SZA cows. Among primiparous cows, AS cows were more likely to become pregnant by 150 DIM than SZA cows. More multiparous cows supplemented with AS tended to be removed from the herd by mid-lactation compared with SZA cows. Urine pH was decreased for AS than SZA cows. No significant differences in milk traits were detected between treatments. These findings indicate that supplementation with SZA before calving can serve as an alternative prevention method to AS to reduce hypocalcemia and improve postpartum health, while not compromising milk production traits or reproductive risk.
Keywords: Disease; Transition period; Dairy cow; Hypocalcemia